Self-reported child abuse in the home: a cross-sectional survey of prevalence, perpetrator characteristics and correlates among public secondary school students in Kathmandu, Nepal - Neupane, Dipika (BMJ Open, 2018)
OBJECTIVES: To explore the prevalence, perpetrator characteristics and the correlates of child abuse in Kathmandu, Nepal. METHODS: For this cross-sectional study, we translated the internationally validated questionnaire developed by the International Society for Prevention of Child Abuse and Neglect, Child Abuse Screening Tool-Child Home into Nepali. We added questions on descriptive information about students and their family to the questionnaire. We recruited students from 20 schools selected randomly—2 from each of the 10 electoral constituencies of Kathmandu district. In each school, we administered the questionnaires to the students in a classroom selected randomly. To assess the correlates, we ran multilevel multivariable logistic regression models, stratified by schools. RESULTS: Among the 962 students, 88.88% had experience of at least one form of abuse throughout their lifetime. Psychological abuse was the most prevalent form of abuse (previous year: 75.19%; lifetime: 76.15%) followed by physical abuse, exposure to violence, neglect and sexual abuse. Adults were the most common perpetrators of child abuse (37.55%). The correlates identified in this study mostly aligned with the global literature on correlates of abuse. Female students were more likely to report neglect (previous year: adjusted OR (AOR) 1.50, 95% CI 1.10 to 2.04; lifetime: AOR 1.49, 95% CI 1.10 to 2.02), but no gender difference was observed with other forms of abuse. Students living with a single parent had a greater likelihood of exposure to violence (previous year: AOR 2.55, 95% CI 1.31 to 4.94; lifetime: AOR 2.77, 95% CI 1.39 to 5.53), neglect (previous year: AOR 2.01, 95% CI 1.10 to 3.69; lifetime: AOR 2.08, 95% CI 1.14 to 3.81) and sexual abuse (previous year: AOR 3.03, 95% CI 1.45 to 6.37; lifetime: AOR 2.49, 95% CI 1.21 to 5.14). CONCLUSIONS: Over 88% of students reported experiencing child abuse in the home in one or more forms throughout their lifetime. Delineating the reasons for the high burden and its implications are important topics for future research.